Demanda hídrica da cultura do meloeiro de acordo com cenários climatológicos utilizando o software cropwat 8.0 - Martins, Danielle da Silva Oliveira (Universidade Federal Rural do Semi-Árido, 2021)
The melon produced at the Jaguaribe-Açu Pole supplies the Brazilian market throughout the year; in addition to the international market, mainly in the off-season in Spain. However, the costs with inputs and irrigation are high, which makes the search for solutions such as the use of simulation models, which allow the knowledge of the water requirement in advance and the yield responses through a tool in a short-term and at a low cost, assisting in management decision making to be adopted, in addition to analyzing the best planting time. The aim of the research was to estimate, through year-by-year simulations of a 31-year historical series (1978 to 2008), the water requirements of the Inodoros and Aromatic melon crops cultivated in the edaphoclimatic conditions of Mossoró - RN, for three seasons of sowing, analyzing the interference of five climatic scenarios in determining the ideal growing season, using the CROPWAT – FAO program as a tool. To determine the water requirement, the methodology proposed by FAO Bulletin No. 56 was followed. The historical series was characterized in five scenarios according to the annual rainfall as follows: Very Dry (VD) up to 365.06 mm; Dry (D) from 365.07 to 551.70 mm; Normal (N) from 551.71 to 885.00 mm; Rainy (R) from 885.01 to 1,046.53 mm and Very Rainy (VR) above 1,046.53 mm. Cropping cycles for the two types of melon started on: June 10 (C-01); September 10 (C-02) and October 10 (C-03), for the sandy clay loam type soil. Cultivation in cycle 01 for rainy years presented the best maximum and minimum temperature values required by melon. The maximum temperature variation over a cycle reached more than 10 ºC. Cultivation in C-01 occurred under unfavorable conditions for melon when in scenario R to VR, where relative humidity exceeded 80%, while in C-02 it was found to be more favorable to the melon crop, followed by C-03 the values obtained for crop Evapotranspiration and accumulated irrigation needs accumulated meet those required by the crop, indicating that the simulations with CROPWAT respond positively to the water demand of the melon, allowing an anticipated view accordingly to the annual climate scenario
Keywords: Cucumis melo L.; Balanço hídrico; Jaguaribe-Açu; Temperatura; Simulação; Cucumis melo L.; water balance; Jaguaribe-Açu; Temperature; Simulation; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO